A JURIDICAL EXAMINATION OF MARRIAGE DISPENSATION AND DIVORCE IN RELIGIOUS COURT; INSIGHTS FROM SADD AL-DZARĪ‘AH - Maryam, Hannat Waladat; F, Fikri; A, Aris; Basri, Rusdaya; Haq, Islamul (Jurnal Al-Dustur, 2024)
Unraveling the intricate dynamics of marriage dispensations and divorces, this study dives deep into the Sidenreng Rappang Religious Court which is located at South Sulawesi, through the lens of Sadd al-Dzarī‘ah. This is a field research study employing a juridical, anthropological, and socio-legal approach. The data analysis utilizes theories of social conflict, law enforcement and sadd al-Dzarī‘ah. Findings indicate that the primary trigger for marriage dispensation applications is premarital pregnancy resulting from free sexual interactions, which neglects children's rights. Law enforcement in cases of divorce following underage marriage reflects justice, certainty, and legal utility without compromising the best interests of underage marriages. The application of sadd al-Dzarī‘ah aims to reduce marriage dispensations and divorces, prioritizing preventive measures and closing opportunities that could harm the future and interests of underage marriages.